سمات الاقتصاد الإسرائيلي ومراحل تطوره - شعبان, إسماعيل; خليل, فادي; عماد, أيهم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن الهدف من البحث محاولة إعطاء نظرة مبسطة عن مراحل تطور الاقتصاد الإسرائيلي منذ قيام الكيان الصهيوني عام 1948 حتى عام 2001، كما يتناول السمات التي تميزت بها كل مرحلة من مراحل تطوره مبيناً نقاط ضعفه ونقاط قوته ومصادر دعم هذا الاقتصاد الذي يعتمد إلى حد كبير على جملة واسعة من المساعدات الخارجية وخاصة الأمريكية والأوروبية و الجباية اليهودية. ويهدف أيضا إلى التأكيد على المقاطعة العربية لإسرائيل كوسيلة ضغط مؤثرة على سياسة إسرائيل ومن يتعاون معها، حيث تعتبر إسرائيل أن مقاومة المقاطعة العربية وإبطال مفعولها هو أحد مهامها الرئيسية الدائمة التي تدخل في معظم مواقفها وعلاقاتها واتصالاتها مع الدول الأخرى. بالإضافة إلى دعم الانتفاضة بشتى الوسائل الممكنة (الاقتصادية والسياسية)، لزيادة آثارها السلبية على الاقتصاد الإسرائيلي. This paper seeks to give a simplified analysis of the stages of development of the Israeli economy since the creation of the Israeli entity in 1948, focusing on the features of each stage, including its weaknesses and strengths as well as the great support and aid it gets from the US, Europe, and Jewish communities worldwide. The paper also tries to emphasize the importance of the Arab boycott of Israel as an effective means of pressure on Israel and its collaborators. This is why resisting Arab boycott and rendering it ineffective are Israel's major permanent goals and are key factors in determining Israel's international attitude and relations. Furthermore, the paper calls for every kind of possible support (economic and political) of the Palestinian uprising (Intifada) to heighten its negative impact on the Israeli economy.